ANALISIS PERAN MOTIVASI DALAM MEMEDIASI HUBUNGAN ANTARA SUPERVISI DAN LINGKUNGAN KERJA DENGAN EFEKTIVITAS KERJA KARYAWAN - Darul Wiyono; Gatot Dwiyono; Ekawati Permana; Hedi Setiadi; Zein Bastian (Cakrawala Management Business Journal, 2022)
The purpose of this study was to determine the role of work motivation in mediating the influence of supervisor/supervision and work environment on the work effectiveness of employees at the Ariyanti Education Foundation. This type of research is quantitative with supervision and work environment as independent variables, motivation as the intervening variable, and work effectiveness as the dependent variable. The number of samples used in this study was 63 from a population of 75, taken with a stratified proportional random sampling technique. The data analysis approach used is Partial Least Square (PLS) analysis: an alternative to Structural Equation Modeling (SEM) with the help of the SmartPLS 3.3.7 statistical application. The results showed that the work motivation variable could well act as a mediation of the influence of supervision/supervision on work effectiveness but the motivational variable was not able to act as a mediation of the influence of the work environment on the work effectiveness of employees.